An Assistive Passive Pelvic Device for Gait Training and Rehabilitation Using Locomotion Dynamic Model - Mokhtarian, A; Fattah, A; Agrawal, S K (Indian journal of science and technology, 2013)
In this paper, we propose the design of a novel gait rehabilitation passive device to training the people who lost their walking ability due to neurological injuries, such as spinal cord injury and stroke. As known, the movements of pelvis play an important role in balance and propulsion during a gait cycle. We simulate a passive orthosis to assist the motion of pelvis of gait patients. We expect that the proposed orthosis, connected to pelvis, assists the patients to regain initial gait pattern by creating the rotations of pelvis close to reference ones during ambulation on treadmill. This optimized pelvic device is un-motorized and contains only optimum passive elements. However, with this device, we consider a Body Weight Support (BWS) to unload a portion of human body weight during treadmill training. The design is accomplished based on a proper dynamic model of human body by focusing on motions of lower leg body segments. The structural configuration of device is determined during an optimization process defined on dynamic model. The simulation results show the time trajectories of pelvic rotations are close to reference trajectories and the optimum passive device can create the desired motion of pelvis without any effort of subject. Also, the results of sensitivity analysis of device by varying the optimum design parameters by 1-3 percent in addition to variation in anthropometry parameters of subject by 1-5 percent show the robust and decent performance of pelvis orthosis during treadmill gait.